Effect of a novel coating material on the microleakage of glass hybrid restoration in primary teeth – An in vitro study - Halah Abdulkareem A. Alkhawaja; Aseel Haidar M.J. Al Haidar (Journal of Baghdad College of Dentistry, 2023)
Background: Glass ionomer restorations are widely employed in the field of pediatric dentistry. There is a constant demand for a durable restoration that remains functional until exfoliation. This study aimed to measure and compare the effect of a novel coating material (EQUIA Forte Coat) on the microleakage of glass hybrid restoration (EQUIA Forte HT) in primary teeth. Material and method: Thirty cavitated (class-II) primary molars were allocated randomly into two groups based on the coat application; uncoated (control) and coated group (experimental). Cavities were prepared by the use of a ceramic bur (CeraBur) and restored with EQUIA Forte HT with or without applying a protective coat (EQUIA Forte Coat). Samples went through the thermocycling process and dipped in 2% methylene blue dye before being sectioned through the center of the restoration. Microleakage was evaluated digitally using software and a camera connected to a stereomicroscope (30 x magnification) to assess dye penetration of the sectioned samples at both the occlusal and gingival marginal levels. Results: There was a significant difference between the coated and uncoated groups at both occlusal (p=.029) and gingival margin sites (p=.001). Conclusion: Higher microleakage values were associated with the uncoated group compared to the coated one. The application of a protective coating to the restorations is an efficient approach to decrease the microleakage of the restorations that can be usefully adopted in clinical practice.